Instruments for Outcome Evaluation of Specific Domains in Primary Sjögren’s Syndrome - Del Papa, Nicoletta (Biomolecules, 2021)
Primary Sjögren’s syndrome (pSS) is a systemic autoimmune disorder characterized by very heterogeneous features. The spectrum of this disorder may vary from benign but disabling symptoms such as dryness, due to lachrymal and salivary involvement, pain and fatigue, to systemic, potentially severe, manifestations that may involve any organ. In recent decades, the arrival of biotechnological therapy has offered new opportunities for the treatment of this—until now—orphan disease. Currently, the possible use of these new drugs in therapeutic trials has made it necessary to have reliable outcome measures to evaluate their efficacy in this disease. A great effort has been made in multicenter, often multinational, studies to develop and validate instruments capable of assessing the different disease-related features. The adoption in therapeutic trials of the newly developed outcome measures aimed at assessing systemic features and patient reported symptoms has often yielded disappointing results. These negative data have been ascribed, on the one hand, to the trial design not being completely appropriate, and, on the other hand, to the fact that a single instrument may be not sufficient to cover the great clinical heterogeneity of the disease features. There is now growing belief that composite end points that include instruments that are able to assess the various aspects of the disease may be more properly and successfully used in future therapeutic trials.